DESAIN PRODUK FESYEN AKSESORIS DENGAN MENGANGKAT BUDAYA LOKAL KALIMANTAN TIMUR - Shiddiq Arifin Dwi Putra; Faza Wahmuda (Jurnal Kreatif : Desain Produk Industri dan Arsitektur, 2021)
Indonesia consists of so many islands and provinces, as well as diverse cultures ranging from Sabang to Merauke. Various cultures that exist in Indonesia, are still preserved by the people who live and live in the area from the past until now as traditions and ancestral heritage that must be preserved. The culture of East Kalimantan is one of the local cultures in Indonesia with distinctive characteristics, namely the culture of the Dayak tribe and the culture of Kutai Kartanegara. In this modern era, many have left the cultural heritage of their ancestors which has become the hallmark of a local identity that exists in Indonesia, especially the East Kalimantan Province. Fashion accessories products are one of the media that can lead the general public to introduce the culture in East Kalimantan with designs that apply elements of local cultural images typical of East Kalimantan. The purpose of designing this fashion accessory product is to pass on a local culture, especially in the East Kalimantan area, which is applied in the form of fashion accessories product media. The research method uses qualitative and quantitative research methods in collecting data. In the analysis there are accessories in the form of needs analysis for fashion products, cultural analysis, shape analysis, glasses system analysis, watch system analysis, bracelet system analysis, material analysis, color analysis, and market analysis. The results of this study are eyewear products with the application of blowpipe shapes, watches products with the application of the Dayak Tribe carving motifs, and products with the application of a combination form of Lembuswana, Hudoq, and Naga Erau.